SPLEEN RUPTURE AS THE FIRST PRESENTATION OF CHRONIC PHASE CHRONIC MYELOID LEUKEMIA. CASE REPORT (Iraqi Journal of Medical Sciences, 2016)
Abstract: Spleen rupture is a rare life threatening emergency that mostly occurs in pathologically enlarged spleens. Causes may include infections, congenital cyst, metabolic, degenerative and malignancy (leukemia). Several possible mechanisms have been proposed for spleen rupture in patients with hematological disorders. Most commonly, malignant cells of lymphoproliferative or myeloproliferative origin infiltrate the spleen directly. Their sheer volume exceeds the capacity of the relatively non-distensible splenic capsule, causing splenic rupture and splenic hemorrhage.In this report we present a 34 years old male patient presented with an acute abdomen after 3 days from sustaining blunt hit over the abdomen. After immediate resuscitation, exploratory laporotomy had done that revealed old altered blood in the peritoneal cavity and large spleen with non-bleeding laceration in addition to hepatomegaly and dilated mesenteric veins. Evacuation of the clotted blood was done with splenectomy.Key word:Massive splenomegaly, chronic myeloid leukemia, spleen rupture
Keywords: Massive splenomegaly; chronic myeloid leukemia; spleen rupture